Wavelet decomposition-NNARX model for flood prediction of Kelantan River, Malaysia - Anuar, Mohd Azrol Syafiee (2018)
Flood is a major disaster that happens around the world. It has caused the loss of many precious lives and massive destruction of property. The possibility of flood can be determined depends on many factors that consist of rainfall, structure of the river, flow rate of the river etc. One of the research challenges is to develop accurate prediction models and what improvement can be made to the forecasting model. The objective of this thesis is to improve the performance of the neural network model to predict the flood on the Kelantan River, Malaysia. A technique for modelling of nonlinear data of flood forecasting using wavelet decomposition-neural network autoregressive exogenous input (NNARX) approach is proposed.